Amerindian time: What does it contribute to theology? - Irarrázaval, Diego (1997)
In the years and centuries to come, as Latin American Catholics we will face immense demands: economic-cultural globalization and endemic impoverishment, multitudes indifferent to the ecclesial, syncretism, a market for religious offerings and an opening to Asian worlds (which are not only quantitative majorities, but also qualified interlocutors in the interreligious reflection of the faith). In the face of all this, in Latin America we must reaffirm our original realities. In this writing I return to the question of "time". It is not an esoteric matter nor is it worth idealizing the autochthonous, it is rather about strengthening the Amerindian being today and thus walking towards the healthy future of all humanity. In theological terms, it is interesting to see the "history of salvation" with Amerindian eyes and rhythms.